MODEL PENELITIAN KALAM; TEOLOGI ISLAM (ILMU KALAM) AHMAD HANAFI - Febri Hijroh Mukhlis (Dialogia, 2015)
Abstract: Ahmad Hanafi intention including one of the pioneers works in the field of theology in Indonesia. His book is oriented to introduce Islamic theology as part of theology to the Indonesian people. According to the method that he applied in, Hanafi divided his theological study into three parts, firstly, talking about the history of development (birth) theology or theology of Islam; secondly, specifically discussing theology streams. Thirdly, discuss some issues theology. The scope of this study is no longer follows the system of theology books that exist. His book only emphasized the problem of theology, without giving any attentions at all to the history. The material sought as far as possible so that each issue is discussed as widely as possible not only limited to a particular stream. The discussions are more comparative, not only between streams of theology itself, but also to the philosophy of Islam. In explaining those, Ahmad Hanafi used historical-comparative method. The writer in this article explains that Ahmad Hanafi tried to deliver or fling theology discourse of development towards more advanced again. In fact, Hanafi discussed about philosophy (Islamic philosophy), as well as the shift of kalam paradigm. Then, the paradigm of shift to kalam theology is followed by the next generations. Keywords: Teologi, Ilmu Kalam, Wujud Tuhan, Al-Ash’ariyah dan Mu’tazilah